Biosphere Reserves: Problems and oportunities in México - Halffter, Gonzalo (Instituto de Ecología, A.C., 2011)
Over the last sixteen years the Federal Government of Mexico has given growing importance to protected natural areas, and particularly the biosphere reserves. In this essay we examine the effect of this support on the biospheres’ fulfilling the different functions outlined by the Seville Strategy, promoted by UNESCO and adopted by member countries. The first reports published on the biodiversity and ecosystem ecology protection in these areas are contradictory and not, in general, very optimistic. Some reserves—especially those that have a laboratory or are associated with a research institute—are very important research centres, and have made a truly important contribution to our knowledge. The incorporation and participation of local communities is improving although there are several aspects that are not yet well developed and in more than one instance there is limited acceptance by the local population. In recent years, there has been notable headway with payment for environmental services. The recommendation that biosphere reserves serve as laboratories for in the search for new alternatives that favour sustainable development at the regional level has not been met; mainly because of the lack of cooperation with other government development programs. It is evident that the biodiversity cannot be effectively protected if no attention is paid to what is happening outside the protected natural areas, thus the last part of the essay deals with rural, ejido, community and private conservation proposals.